Simulations of the linear plasma synthetic jet actuator utilizing a modified Suzen-Huang model - Ibrahim, I. H. (2013)
The linear plasma synthetic jet actuator (L-PSJA) is a unique form of flow control device which harnesses the interaction of induced flows from two linear plasma actuators to form an upward jet. Since each injection can be manipulated in intensity, the synthetic jet has thrust vectoring properties. Our study simulates the L-PSJA by utilizing a modified Suzen-Huang (S-H) model that accounts for drift and diffusive properties in the surface charge. The results of the present model show that the centreline velocity is closer to the experimental values found in literature as compared to the default form of S-H modelling. Thrust vectoring simulations were also performed to demonstrate the feasibility of flow directional variation in the L-PSJA.